SUBSTITUSI SARI BUAH STROBERI TERHADAP MIE BASAH (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2022)
This research is motivated by the absence of the use of natural additives such as strawberries in the wet noodle industry, it is proven that there are still many wet noodles that use artificial ingredients to provide good color, texture and taste and there is no addition of fruits such as strawberries in the wet noodle industry. Wet noodles sold in the market are just ordinary wet noodles with the main ingredients containing carbohydrates without adding other substances. The purpose of this study was to make wet noodles with the addition of strawberry juice, use an alternative to adding strawberry juice to make wet noodles and see how the quality of wet noodles with the addition of strawberry juice in terms of aroma, color, taste and texture. The research method used is the experimental method. Data collection techniques used are literature studies and questionnaires. This research was assessed by expert panelists, namely the Bunda Tourism Academy lecturer, while the general panelists were the surrounding community. The results of the experimental study using organoleptic tests showed that the wet noodles with strawberry juice with a 50% substitution had a fairly strawberry flavored aroma, a less red color, a chewy texture and a fairly strawberry like taste. Strawberry juice wet noodles with 70% substitution with a very strawberry flavored aroma, a red color, a fairly chewy texture and a very strawberry like taste